1984
DOI: 10.1093/nar/12.15.6291
|View full text |Cite
|
Sign up to set email alerts
|

The B–Z transition in two synthetic oligonucleotides: d(C-2-amino-ACGTG) and d(m5CGCAm5CGTGCG) studied by IR, NMR and CD spectroscopies

Abstract: The sequences CA'CGTG (where A' = 2-aminodeoxyadenosine) and m5CGCAm5CGTGCG are prepared and studied by IR, CD and 1H-NMR. Infrared spectra demonstrate the capacity of the modified hexamer and decamer to adopt a Z conformation. The influence of the NH2 substitution on the adenine or of the methylated terminal part of the decamer acting with the increase of the DNA concentration stabilizes the Z conformation at room temperature in low humidity films. Very weak proportion of Z conformation is detected in UV dilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Therefore, in condensed phases, the Z ~coil equilibrium is totally displaced towards the first configuration of d(C-Br"G-C-G-C-Br"G) even at 70°C. Similar effect of the concentration has been previously reported in the case of d(C-2amino A-C-G-T-G) and d(m 5 C-G-C-A-m 5 C-G-T-G-C-G) studied by CD, 1 H-NMR and IR spectroscopic technics (13) which shows that the concentration effect should be important in stabilizing the Z form in biological systems.…”
Section: Kinetic and Thermodynamic Datasupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, in condensed phases, the Z ~coil equilibrium is totally displaced towards the first configuration of d(C-Br"G-C-G-C-Br"G) even at 70°C. Similar effect of the concentration has been previously reported in the case of d(C-2amino A-C-G-T-G) and d(m 5 C-G-C-A-m 5 C-G-T-G-C-G) studied by CD, 1 H-NMR and IR spectroscopic technics (13) which shows that the concentration effect should be important in stabilizing the Z form in biological systems.…”
Section: Kinetic and Thermodynamic Datasupporting
confidence: 85%
“…Recent reports have shown that IR, 1 H-NMR and CD analysis, under various experimental conditions (temperatures, DNA's and ionic concentrations, solvent) of oligonucleotides d(C-Gh containing 5-methyl cytosine residues in different positions (10,12), d(C-2amino A-C-G-T-G) and d(m 5 C-G-C-A-m 5 C-G-T-G-C-G) (13) were effective techniques to study B and Z double helix conformations. In the case of methylated hexamer, the formation of the Z double helix which is dependent on salt concentration was found by 1 H-NMR to take place via formation of a B double helix even in high salt solution (4 M NaCl) (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After zerofilling in the tl dimension, a 1024 x 1024 data point matrix was obtained and then Fourier-transformed in both dimensions. Spectra were line-broadened by a sine bell weighing in both d [15]. In the case of d(C-2aminoA-C-G-T-G) proton assignment was carried out mainly by comparison with d(C-A-C-G-T-G) [8] and by selective protonproton decoupling when necessary.…”
Section: Methodsmentioning
confidence: 99%
“…All oligonucleotides were manually synthesized by the solid-phase phosphotriester method (12) using triisopropylsulfonylnitrotriazole as coupling agent (13) on a 2-mmol scale. The modified nucleoside phosphotriesters t4T, t6G, and n2A have been described (14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%